Decreasing integration within face network and segregation beyond the face network in the aging brain. Issue 4 (22nd May 2022) - Qing, Tianying; Chen, Jing; Xue, Licheng; Tan, Yufei; Huang, Zehao; Yang, Shimeng; Chen, Yuqiu; Wang, Jinhui; Zou, Qihong; Lv, Yating; Zhao, Jing
Abstract: Face processing is known to decline in older adults; however, a clear understanding of the brain networks behind this cognitive decline is still lacking. In this study, we investigated the neural correlates of the declined face processing with aging from a resting‐state brain network perspective. Nineteen healthy old adults and 22 young adults were recruited and underwent two functional magnetic resonance imaging (fMRI) scanning sessions (i.e., resting‐state and localizer task) and two behavioral tests (face matching and symbol‐form matching). We examined age‐related alterations in resting‐state functional connectivity (FC) within face network as well as between face network and other networks, and tested their associations with behavioral performance of face and symbol‐form processing. We found that (a) compared with young adults, old adults exhibited decreased FC between face‐selective regions (fusiform face area and occipital face area), but increased FC between face‐selective regions and non‐face‐selective regions; (b) these age‐related FC alterations were correlated with individuals' behavioral performance of face and symbol‐form processing. Collectively, these findings suggest the declines of face processing are associated with a mixture of decreased integration within the face network and segregation beyond the face network in the aging brain, and provide evidence for a neural basis of cognitive aging in face processing from an intrinsic brain network perspective.